Annulation reaction enables the identification of an exocyclic amide tricyclic chemotype as retinoic acid Receptor-Related orphan receptor gamma (RORγ/RORc) inverse agonists. Issue 19 (1st October 2020) - Marcoux, David; Bertrand, Myra Beaudoin; Weigelt, Carolyn A.; Yip, Shiuhang; Galella, Michael; Park, Hyunsoo; Wu, Dauh-Rurng; Wang, Jinhong; Yarde, Melissa; Cvijic, Mary Ellen; Li, Sha; Hynes, John; et al.
Graphical abstract: Abstract: RORγt is the master regulator of the IL-23/IL-17 axis, a pathway that is clinically validated for the treatment of various immunological disorders. Over the last few years, our group has reported different chemotypes that potently act as inverse agonists of RORγt. One of them, the tricyclic pyrrolidine chemotype, has demonstrated biologic-like preclinical efficacy and has led to our clinical candidate BMS-986251. In this letter, we discuss the invention of an annulation reaction which enabled the synthesis of a tricyclic exocyclic amide chemotype and the identification of compounds with RORγt inverse agonist activity. Preliminary structure activity relationships are disclosed.